A Mixed Method Investigation of Injuries Associated with Artisanal and Small-Scale Mining in Migori County, Kenya - Ajith, Michael Mayom (Curtin University, 2020)
This embedded mixed method research was aimed to investigate the artisanal and small-scale mining related recordable injuries, associated risk factors and socio-economic consequences. 236 participants were surveyed, followed by interviewing of 33 severely injured miners. The results demonstrated that certain personal and operational risk factors influenced the likelihood of injuries, severity and frequency of injuries. Also, severely injured miners experienced negative socio-economic impacts. Improved strategies for injury prevention and post-injury consequences management are advised.